2020
DOI: 10.1007/978-3-030-47436-2_37
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Water Pipe Condition Assessment: A Semiparametric Model Using Gaussian Process and Survival Analysis

Abstract: The maintenance and renewal of water mains demand substantial financial investments, and direct inspection of all water mains in a distribution system is extremely expensive. Therefore, a cost effective break mitigation technique such as a failure forecasting model that allows one to predict the water mains failure likelihood, would reduce the negative social impact and the cost to serve. We introduce a semiparametric Bayesian model for pipeline failure forecasting. The model is centred on a nonparametric Gaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Although only 15 articles have been published in 2021 and 2022, it is expected that the number will exceed that of the previous decade by the end of 2030. This is due to the fact that many utilities are taking proactive measures to construct prediction models for their WDNs (Weeraddana et al., 2020). Furthermore, the emergence of ML‐based models may promote further growth in this domain's publishing.…”
Section: Bibliometric Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Although only 15 articles have been published in 2021 and 2022, it is expected that the number will exceed that of the previous decade by the end of 2030. This is due to the fact that many utilities are taking proactive measures to construct prediction models for their WDNs (Weeraddana et al., 2020). Furthermore, the emergence of ML‐based models may promote further growth in this domain's publishing.…”
Section: Bibliometric Analysismentioning
confidence: 99%
“…According to the American Water Work Association (AWWA), the USA needs to invest around $1 trillion in replacing and repairing the deteriorating components of their WDNs (Fan et al, 2022). In Australia, the estimated cost of repairing and maintaining WDNs is about AUD 1.4 billion (Weeraddana et al, 2020). In South Korea, 52.5% of the water pipes will require rehabilitation by 2024, as indicated in a study by Seo et al (2015).…”
mentioning
confidence: 99%
“…Most of the research found in the literature predict short-term failure forecasting, which spans 1-3 years into the future [12]. However, water utilities require long-term estimations for the structural deterioration of water mains to effectively plan the renewal of water distribution systems and to develop a risk based investment decisions for capital interventions [24]. Therefore, the main objective of this work is to investigate pipe failure factors and develop a long-term prediction model.…”
Section: Related Workmentioning
confidence: 99%